PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KOMPETENSI GURU, DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN WONOSARI KABUPATEN GUNUNGKIDUL TAHUN PELAJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This study aimed at determining the influence of principal leadership, teacher competency, and school culture either simultaneously or individually on the performance of junior high school teachers in the district of Wonosari Gunungkidul regency. This study adopted a quantitative approach. The study population was junior high school teachers in the district of Wonosari Gunungkidul regency. The sampling technique used was proportional random sampling. Data was obtained through a questionnaire that had been tested and met the requirements of validity and reliability. Techniques of data analysis performed in this study were: (1) descriptive analysis of the data, (2) analysis oftest requirements including: normality test, linearity and multicolinearity test, (3) test of hypothesis using multiple linear regression analysis and partial correlation. Conclusions of this study were: (1) principal leadership, teacher competency, and school culture simultaneously had a positive and significant influence on teacher performance. Principal leadership variables contribute most to the performance of teachers, with the effective contribution of 43.8%, school culture variables of 26.9% and teacher competency variables of 9.9%, (2) principal leadership had a positive and significant impact on teacher performance, (3) teacher performance had a positive and significant impact on teacher performance, (4) school culture had a positive and significant impact on teacher performance.